2017
DOI: 10.1007/s13224-017-1010-7
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Versus Bilateral Laparoscopic Ovarian Drilling Using Thermal Dose Adjusted According to Ovarian Volume in CC-Resistant PCOS, A Randomized Study

Abstract: Bilateral laparoscopic ovarian drilling with thermal dose adjusted according to ovarian volume is more effective than the right-sided unilateral technique with thermal dose adjusted according to ovarian volume in terms of menstrual cycle resumption, ovulation and cumulative pregnancy rates in CC-resistant PCOS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Furthermore, risk of publication bias must also be taken into account. Last but not least, neither the CC-stimulation regimen nor CC resistance was defined in detail in the majority of included studies [6,7,28,29]. In our data set, CC was started on cycle day 4 or 5, which is not in accordance with the majority of recently published studies [45].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Furthermore, risk of publication bias must also be taken into account. Last but not least, neither the CC-stimulation regimen nor CC resistance was defined in detail in the majority of included studies [6,7,28,29]. In our data set, CC was started on cycle day 4 or 5, which is not in accordance with the majority of recently published studies [45].…”
Section: Discussionmentioning
confidence: 93%
“…The latter might include differences in patient characteristics. For example, other studies than ours included more women with a BMI > 30 kg/m 2 [6,28,29]. This might have introduced minor deviances, as it could have been the case with differences in study quality.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Bilateral LOD using fixed monopolar diathermy energy is the standard method, however, with a lack of consensus regarding how much energy to use [4]. Some studies have been reported of unilateral LOD with fixed or adjusted diathermy [5,6] and various numbers of punctures [7,8].…”
mentioning
confidence: 99%